PROFIL PEREMPUAN BURUH GENDONG DI PASAR BERINGHARJO KOTA YOGYAKARTA - , Istiatun, Dra. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The work of porters women in the traditional markets in Special Region of Yogyakarta shows the diversity of alternative work in one perspective. However, in another aspect it depicts the economic pressure that makes women to work outside in order to meet their house holds' need. This porters women group can be seen as marginal in economic, education, politics and culture. Nevertheless, this group still exists amid the modernization of Beringharjo market of Yogyakarta. The issue in this research will focus on the profile and the relationship among each other, including other groups. This research is done by using qualitative-descriptive approach. Gathering the data by using techniques of: observation, documentation, interview and Focus Group Discussion